Introductory social studies create. (Chicago : Encyclopaedia Britannica, 2001)
Contains activities designed to guide students through specific Internet sites related to social studies and help them better understand the information they are viewing.
"Introductory Internet activities"--Cover.
Cover title: Social studies explore create.
Title from cover p. [4].
Professional
Keywords: Social sciences -- Computer-assisted instruction; Social sciences -- Study and teaching; Social sciences -- Computer-assisted instruction; Social sciences -- Study and teaching